Green wear-resistant cement concrete pavement material and preparation method thereof
By using ingredients such as cement, palm oil fuel ash, nano-silica, modified waste polypropylene fiber and modified crumb rubber particles in pavement materials, the problem of insufficient wear resistance of pavement materials has been solved, and higher wear resistance has been achieved. grinding performance and longer road service life, while also having the advantages of environmental protection and resource saving.
Patent Information
- Application Number
- CN202411907029.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The wear resistance of existing pavement materials is insufficient, resulting in problems such as depression and cracking on the road surface, affecting driving safety and road service life.
The composition of green wear -resistant cement concrete pavement material includes cement, palm oil fuel gray, nano -silica dioxide, modified waste polypropylene fiber, river sand, modified fragmented rubber particles, gravel, water, polycarboxylic acid High -efficiency water reducing agent and trimethalamine. Mixing, modified treatment, and uniform mixing through dry mixing, improving the adhesion and abrasion resistance of the material.
This material can not only save natural resources, reduce environmental pollution and carbon dioxide emissions, but also significantly improve the wear resistance of concrete and extend the service life of roads.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of road surface materials, and in particular to a green wear-resistant cement concrete road surface material and a preparation method thereof. Background Art
[0002] Solid waste refers to non-reusable solid materials generated by production, construction, maintenance and other activities, which will cause environmental pollution and waste of resources. Finding an effective waste resource utilization technology has become an important issue in current environmental protection and resource conservation. The combination of waste and concrete is an effective waste resource utilization technology. Combining waste with concrete forms a new type of concrete material. This green concrete can not only reduce environmental pollution and save resources, but also improve the performance of concrete through mutual synergy.
[0003] As the speed and transportation volume of heavy-duty vehicles increase, the wear of concrete components such as highway pavements, bridge decks and airport pavements increases, causing the pavement to be prone to dents, cracks and other problems. The pavement mainly bears impact loads and tire friction. Good wear resistance can enhance the friction between automobile tires and the road surface, improve driving safety and road service life. Summary of the invention
[0004] The present invention aims to realize the resource utilization of solid waste and solve the problem of insufficient wear resistance of pavement materials, and provides a green wear-resistant cement concrete pavement material and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A green wear-resistant cement concrete pavement material, the components and their weight parts are:
[0007] 315-405 parts of cement, 45-135 parts of palm oil fuel ash, 4.5-13.5 parts of nano silicon dioxide, 2.4-7.2 parts of modified waste polypropylene fiber, 595-765 parts of river sand, 85-255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 3.4-4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.25-2.5 parts of triethanolamine.
[0008] The palm oil fuel ash is obtained by sieving through a 300-mesh square hole sieve and removing foreign matter and coarse particles therein, and has a specific gravity of 2.1-2.4.
[0009] The modified waste polypropylene fiber comes from the multi-filament polypropylene fiber waste of the textile factory. The multi-filament polypropylene fiber waste is cut to obtain waste polypropylene fiber with a length of 20mm, an aspect ratio of 440, and a density greater than 900kg / m 3 , tensile strength is greater than 400MPa.
[0010] The modification steps of modified waste polypropylene fiber are:
[0011] The surface of the concrete was modified before mixing. The cut waste polypropylene fibers were immersed in 80°C xylene solution for 60 minutes. The waste polypropylene fibers were taken out and washed with acetone for three times. Ethanol and water were mixed in a ratio of 9:1, and a silane coupling agent with a concentration of 20% was added to prepare a modified solution. The waste polypropylene fibers were immersed in the modified solution for 30 minutes, and the modified waste polypropylene fibers were prepared after drying.
[0012] The modified crushed rubber particles come from waste tires or waste rubber shoes. The waste tires or waste rubber shoes are mechanically crushed and sieved into three particle sizes of crushed rubber particles, which are 0.6-1.18mm, 1.18-2.36mm, and 2.36-4.75mm respectively. The mass ratio of the three particle sizes of crushed rubber particles is 2:2:1.
[0013] The modification steps of modified crumb rubber particles are:
[0014] 100 parts of crushed rubber particles were soaked in a 10% by mass sodium hydroxide solution for 12 hours, washed and dried, added to an 80% by mass ethanol solution, 50 parts of ethyl orthosilicate and 0.5 parts of ammonia water were mixed, and the mixed solution was added to the ethanol solution, stirred for 2 minutes, and dried to obtain modified crushed rubber particles.
[0015] The particle size range of river sand is 0-4.75mm.
[0016] The crushed stone particle size ranges from 5 to 20 mm.
[0017] The above-mentioned method for preparing a green wear-resistant cement concrete pavement material comprises the following steps:
[0018] S1. Dry-mixing cement, palm oil fuel ash and nano-silicon dioxide for 1 min to obtain a first mixture;
[0019] S2, mixing polycarboxylic acid high-efficiency water reducer, triethanolamine and water and stirring for 1 min to obtain a mixed solution;
[0020] S3, adding river sand and modified crushed rubber particles to the first mixture and stirring for 2 minutes, and then adding crushed stone and stirring for 2 minutes to obtain a second mixture;
[0021] S4, adding the modified waste polypropylene fiber to the second mixture in small amounts and multiple times while stirring, stirring for 2 min-3 min, to obtain a third mixture;
[0022] S5. Pour the mixed solution evenly into the third mixture and stir for 2 minutes to obtain a green wear-resistant cement concrete pavement material.
[0023] The beneficial effects of the present invention are as follows: the present invention prepares green wear-resistant cement concrete based on wastes such as palm oil fuel ash, multi-filament polypropylene fiber waste from textile factories and waste rubber, which can not only save natural resources, but also reduce environmental pollution and carbon dioxide emissions, and further cooperate with cement-based materials to improve concrete performance; in the present invention, the silane coupling agent undergoes a self-hydrolysis reaction on the surface of the polypropylene fiber and is wrapped on the surface of the fiber, and the hydrophilic property of the surface of the polypropylene fiber is improved through the polar hydrophilic functional groups of the silane coupling agent itself; ethyl orthosilicate undergoes hydrolysis-condensation under alkaline conditions to generate a layer of continuous material on the surface of the waste rubber particles Coated on the surface of particles, more SiO2 inorganic matter is formed and agglomerated, which is adsorbed on the surface of particles. SiO2 has strong hydrophilicity, and the modification of both from hydrophobic to hydrophilic greatly improves the interfacial bonding force with cement mortar. The rubber particles in the present invention increase the contact area between vehicle tires and fine aggregates, and the friction coefficient between rubber and rubber is higher, which increases the anti-skid property of concrete. Polypropylene fibers connect cement slurry and aggregate particles through bridging effect, which enhances the toughness of concrete and reduces road wear. Palm oil fuel ash and nano-silicon dioxide act as activators to strengthen the bonding between rubber particles, fibers and mortar, improve the strength and density of concrete, and enhance the wear resistance of concrete. DETAILED DESCRIPTION
[0024] The principles and features of the present invention are described below in conjunction with specific embodiments. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention. The advantages and features of the present invention will become more apparent from the following description.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0026] The present invention will be further described below in conjunction with specific embodiments:
[0027] A green wear-resistant cement concrete pavement material, the components and their weight parts are:
[0028] 315-405 parts of cement, 45-135 parts of palm oil fuel ash, 4.5-13.5 parts of nano silicon dioxide, 2.4-7.2 parts of modified waste polypropylene fiber, 595-765 parts of river sand, 85-255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 3.4-4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.25-2.5 parts of triethanolamine.
[0029] The palm oil fuel ash is obtained by sieving through a 300-mesh square hole sieve and removing foreign matter and coarse particles therein, and has a specific gravity of 2.1-2.4.
[0030] Palm oil fuel ash partially replaces cement. As an agricultural waste, palm fuel ash is a volcanic ash material rich in silica. It can replace cement as a cementitious material, reduce the amount of cement used in concrete, and make resourceful use of palm fuel ash.
[0031] The modified waste polypropylene fiber comes from the multi-filament polypropylene fiber waste of the textile factory. The multi-filament polypropylene fiber waste is cut to obtain waste polypropylene fiber with a length of 20mm, an aspect ratio of 440, and a density greater than 900kg / m 3 , tensile strength is greater than 400MPa.
[0032] The modification steps of modified waste polypropylene fiber are:
[0033] The surface of the concrete was modified before mixing. The cut waste polypropylene fibers were immersed in 80°C xylene solution for 60 minutes. The waste polypropylene fibers were taken out and washed with acetone for three times. Ethanol and water were mixed in a ratio of 9:1, and a silane coupling agent with a concentration of 20% was added to prepare a modified solution. The waste polypropylene fibers were immersed in the modified solution for 30 minutes, and the modified waste polypropylene fibers were prepared after drying.
[0034] The silane coupling agent undergoes a self-hydrolysis reaction on the surface of the xylene polypropylene fiber and wraps around the fiber surface, and carbonyl groups appear on the fiber surface. The modification of the silane coupling agent brings polar groups to the fiber surface and greatly reduces the filaments on the fiber surface. The polar hydrophilic functional groups of the silane coupling agent itself improve the hydrophilic properties of the polypropylene fiber surface and enhance the bonding force between the polypropylene fiber and the cement-based material.
[0035] Modified waste polypropylene fibers connect cement paste and aggregate particles through bridging effect, enhancing the toughness of concrete and reducing road wear.
[0036] The modified crushed rubber particles come from waste tires or waste rubber shoes. The waste tires or waste rubber shoes are mechanically crushed and sieved into three particle sizes of crushed rubber particles, which are 0.6-1.18mm, 1.18-2.36mm, and 2.36-4.75mm respectively. The mass ratio of the three particle sizes of crushed rubber particles is 2:2:1.
[0037] The modification steps of modified crumb rubber particles are:
[0038] 100 parts of crushed rubber particles were soaked in a 10% by mass sodium hydroxide solution for 12 hours, washed and dried, added to an 80% by mass ethanol solution, 50 parts of ethyl orthosilicate and 0.5 parts of ammonia water were mixed, and the mixed solution was added to the ethanol solution, stirred for 2 minutes, and dried to obtain modified crushed rubber particles.
[0039] There will be a certain number of hydroxyl groups on the surface of the crumb rubber particles treated with sodium hydroxide. During the hydrolysis of ethyl orthosilicate, a large number of Si(OH)4 molecules are combined on the surface of the rubber powder particles, and then condensed to form a Si-O inorganic network structure. A layer of SiO2 with a -Si-O-Si- network structure is formed on the surface, which is highly hydrophilic and has a large number of hydroxyl groups. The contact angle of the modified crumb rubber particles with water is reduced from 95° to 24°, and the surface changes from hydrophobic to hydrophilic, which improves the interfacial bonding force with the building mortar.
[0040] The modified crushed rubber particles increase the contact area between vehicle tires and fine aggregates, the friction coefficient between rubber and rubber is higher, and the anti-slip property of concrete is increased. When the above particle size and proportion are used, the flow properties and road performance of concrete are better.
[0041] The particle size range of river sand is 0-4.75mm.
[0042] The crushed stone particle size ranges from 5 to 20 mm.
[0043] The above-mentioned method for preparing a green wear-resistant cement concrete pavement material comprises the following steps:
[0044] S1. Dry-mixing cement, palm oil fuel ash and nano-silicon dioxide for 1 min to obtain a first mixture;
[0045] S2, mixing polycarboxylic acid high-efficiency water reducer, triethanolamine and water and stirring for 1 min to obtain a mixed solution;
[0046] S3, adding river sand and modified crushed rubber particles to the first mixture and stirring for 2 minutes, and then adding crushed stone and stirring for 2 minutes to obtain a second mixture;
[0047] S4, adding the modified waste polypropylene fiber to the second mixture in small amounts and multiple times while stirring, stirring for 2 min-3 min, to obtain a third mixture;
[0048] S5. Pour the mixed solution evenly into the third mixture and stir for 2 minutes to obtain a green wear-resistant cement concrete pavement material.
[0049] The dry powder is fully mixed to ensure the uniformity of each phase of cementitious materials, and then river sand, modified crushed rubber particles and crushed stone are added to make the aggregate fully wrapped by the cementitious materials. Modified waste polypropylene fibers are added in small amounts and multiple times to facilitate the uniform dispersion of the fiber phase in the concrete. The water reducer and activator are mixed before water to further improve the activity of the cementitious materials and enhance the strength and comprehensive performance of the concrete.
[0050] The present invention is further described in detail below in conjunction with specific examples. It is particularly noted that if no specific conditions are specified in the following specific examples, the processes are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following specific examples can all be sourced from common commercial sources.
[0051] In each specific embodiment and comparative example of the present invention, the same raw materials used are all from the same batch.
[0052] In the following specific embodiments and comparative examples, PO42.5 ordinary Portland cement is used as cement.
[0053] Palm oil fuel ash is the industrial waste left by palm oil mills using palm fiber and palm husk to generate electricity. The chemical composition is shown in Table 1.
[0054]
[0055] Modified crushed rubber particles are made from waste tires by cutting and crushing, and are mechanically crushed and sieved into three particle sizes: 0.6-1.18mm, 1.18-2.36mm, and 2.36-4.75mm.
[0056] The particle size range of river sand is 0-4.75mm.
[0057] The crushed stone particle size ranges from 5 to 20 mm.
[0058] The nano silicon dioxide may be AEROSIL 380 produced by Evonik.
[0059] The modified waste polypropylene fiber is obtained by cutting the multi-filament polypropylene fiber waste from the textile factory. The length is 20mm, the aspect ratio is 440, and the density is greater than 900kg / m 3 , tensile strength is greater than 400MPa.
[0060] The water reducer is polycarboxylic acid high performance water reducer HLX (standard type).
[0061] Sodium hydroxide, tetraethyl orthosilicate, ethanol, ammonia water, silane coupling agent KH-570, xylene, acetone, and triethanolamine were all analytically pure, and the water used in the modification process was deionized water.
[0062] The water used for mixing concrete is tap water.
[0063] The mixer used in the test specimen molding process was a single-shaft concrete mixer (60L).
[0064] The tests on sampling, forming and curing of raw materials for test specimens shall refer to the relevant provisions of "Test Code for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020).
[0065] The test items for the performance of the test specimens include compressive strength, tensile strength, elastic modulus, wear and anti-slip performance.
[0066] In the following specific examples 1-3 and comparative examples 1-3, the modified waste polypropylene fiber includes the following steps: surface modification is performed before concrete mixing, and the cut waste polypropylene fiber is immersed in an 80° C. xylene solution for 60 minutes; the waste polypropylene fiber is taken out and washed three times with acetone; ethanol and water are mixed in a ratio of 9:1, and a silane coupling agent with a concentration of 20% is added to prepare a modified solution; the waste polypropylene fiber is immersed in the modified solution for 30 minutes, and the modified waste polypropylene fiber is prepared after drying.
[0067] In the following specific examples 1-3 and comparative examples 1-3, the modified crumb rubber particles include the following steps: 100 parts of crushed crumb rubber particles are placed in a 10% by mass sodium hydroxide solution and soaked for 12 hours, washed and dried, added to an 80% by mass ethanol solution, 50 parts of ethyl orthosilicate and 0.5 parts of ammonia water are mixed, and the mixed solution is added to the ethanol solution, stirred for 2 minutes, and dried to obtain modified crumb rubber particles. Specific embodiment 1
[0069] The green wear-resistant cement concrete pavement material in this embodiment includes the following raw materials in parts by weight: 405 parts of cement, 45 parts of palm oil fuel ash, 4.5 parts of nano-silicon dioxide, 2.4 parts of modified waste polypropylene fiber, 765 parts of river sand, 85 parts of modified crushed rubber particles, 860 parts of gravel, 220 parts of water, 3.4 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.25 parts of triethanolamine.
[0070] The preparation method is:
[0071] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and modified crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; modified waste polypropylene fiber is added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain a green wear-resistant cement concrete pavement material.
[0072] During the preparation process of this embodiment, the stirring shaft speed of the vibration stirrer is 45±2 r / min. Specific embodiment 2
[0074] The green wear-resistant cement concrete pavement material in this embodiment includes the following raw materials in parts by weight: 360 parts of cement, 90 parts of palm oil fuel ash, 9 parts of nano-silicon dioxide, 4.8 parts of modified waste polypropylene fiber, 676 parts of river sand, 169 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 3.95 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.35 parts of triethanolamine.
[0075] The preparation method is:
[0076] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and modified crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; modified waste polypropylene fiber is added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain a green wear-resistant cement concrete pavement material.
[0077] During the preparation process of this embodiment, the stirring shaft speed of the vibration stirrer is 45±2 r / min. Specific embodiment 3
[0079] The green wear-resistant cement concrete pavement material in this embodiment includes the following raw materials in parts by weight: 315 parts of cement, 135 parts of palm oil fuel ash, 13.5 parts of nano-silicon dioxide, 7.2 parts of modified waste polypropylene fiber, 595 parts of river sand, 255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.5 parts of triethanolamine.
[0080] The preparation method is:
[0081] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and modified crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; modified waste polypropylene fibers are added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain the green wear-resistant cement concrete pavement material.
[0082] During the preparation process of this embodiment, the stirring shaft speed of the vibration stirrer is 45±2 r / min.
[0083] Comparative Example 1
[0084] The cement concrete pavement material in this comparative example includes the following raw materials in parts by weight: 450 parts of cement, 13.5 parts of nano-silicon dioxide, 7.2 parts of modified waste polypropylene fibers, 595 parts of river sand, 255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.5 parts of triethanolamine.
[0085] The preparation method is:
[0086] The required amount of cement and nano-silicon dioxide are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducing agent, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and modified crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; modified waste polypropylene fiber is added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain the cement concrete pavement material.
[0087] During the preparation of this comparative example, the stirring shaft speed of the vibration mixer was 45±2 r / min.
[0088] Comparative Example 2
[0089] The cement concrete pavement material in this comparative example includes the following raw materials in parts by weight: 315 parts of cement, 135 parts of palm oil fuel ash, 13.5 parts of nano silicon dioxide, 595 parts of river sand, 255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.5 parts of triethanolamine.
[0090] The preparation method is:
[0091] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and modified crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; the mixed solution is evenly poured into the second mixture and stirred for 2 minutes to obtain the cement concrete pavement material.
[0092] During the preparation of this comparative example, the stirring shaft speed of the vibration mixer was 45±2 r / min.
[0093] Comparative Example 3
[0094] The cement concrete pavement material in this comparative example includes the following raw materials in parts by weight: 315 parts of cement, 135 parts of palm oil fuel ash, 13.5 parts of nano silicon dioxide, 7.2 parts of modified waste polypropylene fiber, 850 parts of river sand, 860 parts of crushed stone, 220 parts of water, 4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.5 parts of triethanolamine.
[0095] The preparation method is:
[0096] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and crushed stone are mixed and stirred for 2 minutes to obtain a second mixture; modified waste polypropylene fiber is added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain the cement concrete pavement material.
[0097] During the preparation of this comparative example, the stirring shaft speed of the vibration mixer was 45±2 r / min.
[0098] Comparative Example 4
[0099] The cement concrete pavement material in this comparative example includes the following raw materials in parts by weight: 315 parts of cement, 135 parts of palm oil fuel ash, 13.5 parts of nano silicon dioxide, 7.2 parts of waste polypropylene fiber, 595 parts of river sand, 255 parts of crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.5 parts of triethanolamine.
[0100] The preparation method is:
[0101] The required amounts of cement, palm oil fuel ash and nano-silica are dry-mixed and stirred for 1 minute to obtain a first mixture; polycarboxylic acid high-efficiency water reducer, triethanolamine and water are mixed and stirred for 1 minute to obtain a mixed solution; river sand and crushed rubber particles are added to the first mixture and stirred for 2 minutes, and then crushed stone is added and stirred for 2 minutes to obtain a second mixture; waste polypropylene fiber is added to the second mixture in small amounts and multiple times while stirring, and stirred for 2 minutes to 3 minutes to obtain a third mixture; the mixed solution is evenly poured into the third mixture and stirred for 2 minutes to obtain the cement concrete pavement material.
[0102] During the preparation of this comparative example, the stirring shaft speed of the vibration mixer was 45±2 r / min.
[0103] The results of the performance tests of specific embodiments 1-3 and comparative examples 1-4 are shown in Table 2.
[0104]
[0105] As shown in Table 2, the mechanical properties of specific embodiments 1-3 can meet the design bending tensile strength of Class IV highway, and the wear amount of the road surface is ≤3.0kg / m 2 , which can meet the design requirements of first-class highways. From the various properties of specific embodiments 1-3, it is found that with the increase of the amount of palm oil fuel ash, modified waste polypropylene fiber, and modified waste rubber particles, the compressive strength is reduced, the tensile strength is gradually increased, the wear amount is gradually reduced, and the BPN value is gradually increased. Under the premise of meeting the requirements of mechanical properties, the present invention appropriately reduces the mechanical indicators, greatly enhances the anti-skid and wear-resistant properties of the road surface, and can extend the service life of the highway.
[0106] From the comparison between specific example 3 and comparative example 1, it can be seen that in the absence of palm oil fuel ash, the compressive strength of concrete is reduced, the tensile strength is reduced, the elastic modulus is reduced, the wear amount is increased, and the BPN value is reduced. The main component of palm oil fuel ash is silicon dioxide, with a content of 43%-71%. Under the action of the activator, it has a good pozzolanic reaction and is an excellent cement substitute.
[0107] From the comparison of specific embodiment 3 and comparative example 2, it can be obtained that the lack of modified waste polypropylene fiber leads to a decrease in the compressive strength of concrete, a decrease in tensile strength, a decrease in elastic modulus, an increase in wear, and a decrease in BPN value. The elastic modulus of the fiber is higher than that of the concrete and strengthens the transition zone between the cement mortar. The lack of fiber leads to a decrease in the compressive strength, tensile strength, elastic modulus, wear resistance and anti-slip properties of the concrete.
[0108] From the comparison of specific embodiment 3 and comparative example 3, it can be obtained that in the absence of modified waste rubber particles, the compressive strength of concrete is slightly increased, the tensile strength is reduced, the elastic modulus is reduced, the wear amount is increased, the BPN value is reduced, and the mechanical properties of rubber are not as good as river sand, but the friction coefficient between rubber and rubber is higher. Therefore, the lack of modified waste rubber particles increases the mechanical properties of concrete, and the wear resistance of the pavement is reduced.
[0109] From the comparison between the specific example 3 and the comparative example 4, it can be seen that without modifying the waste polypropylene fiber and the waste rubber particles, the various properties of the mixture are reduced. Since the fiber and rubber are hydrophobic, they cannot form an effective bond with the cement mortar, and are prone to debonding and slippage, which makes it easier for the fiber and rubber to separate from the cement mortar, resulting in a reduction in the overall mechanical properties and road performance.
[0110] From the above results, it can be seen that the road surface material provided by the present invention has good mechanical properties and wear resistance. At the same time, the raw materials involved in the present invention are palm oil fuel ash, waste polypropylene fibers, and waste rubber particles, which are low in cost, green and environmentally friendly, and fully develop solid waste.
[0111] The present invention has been exemplarily described above in conjunction with specific embodiments. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various improvements are made using the method concept and technical solution of the present invention, or they are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A green wear-resistant cement concrete pavement material, characterized in that: The components and their weight parts are: 315-405 parts of cement, 45-135 parts of palm oil fuel ash, 4.5-13.5 parts of nano silicon dioxide, 2.4-7.2 parts of modified waste polypropylene fiber, 595-765 parts of river sand, 85-255 parts of modified crushed rubber particles, 860 parts of crushed stone, 220 parts of water, 3.4-4.5 parts of polycarboxylic acid high-efficiency water reducing agent, and 2.25-2.5 parts of triethanolamine.
2. The green wear-resistant cement concrete pavement material according to claim 1, characterized in that: The palm oil fuel ash is obtained by sieving through a 300-mesh square-hole sieve and removing foreign matter and coarse particles therefrom, and has a specific gravity of 2.1-2.
4.
3. The green wear-resistant cement concrete pavement material according to claim 1, characterized in that: The modified waste polypropylene fiber comes from the multi-filament polypropylene fiber waste of the textile factory. The multi-filament polypropylene fiber waste is cut to obtain waste polypropylene fiber with a length of 20mm, an aspect ratio of 440, and a density greater than 900kg / m 3 , tensile strength is greater than 400MPa.
4. The green wear-resistant cement concrete pavement material according to claim 3 is characterized in that: The modification steps of modified waste polypropylene fiber are: The surface of the concrete was modified before mixing. The cut waste polypropylene fibers were immersed in 80°C xylene solution for 60 minutes. The waste polypropylene fibers were taken out and washed with acetone for three times. Ethanol and water were mixed in a ratio of 9:1, and a silane coupling agent with a concentration of 20% was added to prepare a modified solution. The waste polypropylene fibers were immersed in the modified solution for 30 minutes, and the modified waste polypropylene fibers were prepared after drying.
5. The green wear-resistant cement concrete pavement material according to claim 1, characterized in that: The modified crushed rubber particles come from waste tires or waste rubber shoes. The waste tires or waste rubber shoes are mechanically crushed and sieved into three particle sizes of crushed rubber particles, which are 0.6-1.18mm, 1.18-2.36mm, and 2.36-4.75mm respectively. The mass ratio of the three particle sizes of crushed rubber particles is 2:2:
1.
6. The green wear-resistant cement concrete pavement material according to claim 5, characterized in that: The modification steps of modified crumb rubber particles are: 100 parts of crushed rubber particles were soaked in a 10% by mass sodium hydroxide solution for 12 hours, washed and dried, added to an 80% by mass ethanol solution, 50 parts of ethyl orthosilicate and 0.5 parts of ammonia water were mixed, and the mixed solution was added to the ethanol solution, stirred for 2 minutes, and dried to obtain modified crushed rubber particles.
7. The green wear-resistant cement concrete pavement material according to claim 1, characterized in that: The particle size range of river sand is 0-4.75mm.
8. The green wear-resistant cement concrete pavement material according to claim 1, characterized in that: The crushed stone particle size ranges from 5 to 20 mm.
9. A method for preparing the green wear-resistant cement concrete pavement material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Dry-mixing cement, palm oil fuel ash and nano-silicon dioxide for 1 min to obtain a first mixture; S2, mixing polycarboxylic acid high-efficiency water reducer, triethanolamine and water and stirring for 1 min to obtain a mixed solution; S3, adding river sand and modified crushed rubber particles to the first mixture and stirring for 2 minutes, and then adding crushed stone and stirring for 2 minutes to obtain a second mixture; S4, adding the modified waste polypropylene fiber to the second mixture in small amounts and multiple times while stirring, stirring for 2 min-3 min, to obtain a third mixture; S5. Pour the mixed solution evenly into the third mixture and stir for 2 minutes to obtain a green wear-resistant cement concrete pavement material.
Citation Information
Patent Citations
Waste polypropylene fiber rubber recycled concrete and preparation method thereof
CN105060785A